Thematic Approach to Negatively Judged Kazakh Proverbs - Ospanova, Gülmira (Fırat University, 2026)
Proverbs that exist in every culture are wise sayings that express general rules and judgments. These sayings, which are as old as human history, are not only traditionally instructive and commonly accepted principles, but also noteworthy for having contradictory meanings. For instance, while the proverb “Xan jarlığınan qatın jarlığı küşti” (“A woman’s command is stronger than a khan’s command”) glorifies women, the proverb “Qatın aqılsız, baqa quyryqsız” (“A woman without wisdom is like a frog without a tail”) clearly aims to belittle them. Similarly, the proverb “Jigitke jeti öner de az” (Seven skills are not enough for a young man) encourages learning skills and crafts, where as “Artıq öner bas joyadı” (“Too much skill can ruin a person”) promotes laziness and contentment with less. This study aims to draw attention to contradictory or negatively judgmental proverbs in Kazakh Turkic by analyzing them semantically. Negatively judgmental Kazakh proverbs, collected through a review of various sources, have been categorized according to their themes. Proverbs related to women; relatives and kinship; money, wealth and poverty; greed and self-interest and religion as well as negative judgments are examined, along with theire quivalents in Turkish. The study concludes that negatively judgmental proverbs reflect the view point and approach of a specific segment of society in a given situation. It also aims to carry out a comparative investigation of similar examples in historical and contemporary Turkic dialects.

Her kültürde var olan atasözleri, genel kural ve yargı bildiren bilgece sözlerdir. İnsanlık tarihi kadar eski olan bu sözlerin, alışılagelen öğretici ve genel geçer kural olmalarının dışında zıt anlam değerlerine sahip olmaları da dikkat çekicidir. Öyle ki örneğin, kadını yücelten ‘Xan jarlığınan qatın jarlığı küşti.’ (Hanın fermanından hatunun fermanı daha güçlüdür.) şeklindeki atasözüne karşın ‘Qatın aqılsız, baqa quyrıqsız.’ (Kadın akılsız, kurbağa kuyruksuz.) atasözünün kadını aşağılamak için söylendiği ortadadır. ‘Jigitke jeti öner de az.’ (Delikanlıya yedi hüner de az.) şeklindeki atasözü, hüner ve sanat öğrenmeye teşvik ederken, ‘Artıq öner bas joyadı.’ (Fazla hüner, insanı başından eder.) atasözü ise tembelliği ve azla yetinmeyi hoş karşılamaya sevk eden sözlerdendir. Kazak Türkçesindeki çelişkili veya olumsuz yargılı atasözlerine dikkat çekmeyi amaçlayan bu çalışmada, bu tür atasözleri anlamsal bakımdan incelenir. Çeşitli kaynaklar taranmak suretiyle elde edilen olumsuz yargılı Kazak atasözleri konularına göre gruplandırıldı. Kadın; akraba ve hısım; para, zenginlik ve fakirlik; açgözlülük ve menfaat; dinî içerikli olumsuz yargılı atasözleri ele alınarak Türkiye Türkçesindeki karşılıkları da verildi. Olumsuz yargılı atasözlerinin belirli bir durum karşısında toplumun belirli bir kesiminin o anki görüş ve yaklaşımını yansıttığı sonucuna varılan bu çalışmayla, tarihî ve çağdaş Türk lehçelerindeki emsallerinin karşılaştırmalı araştırılması da amaçlanmaktadır.
Olumsuz Yargılı Kazak Atasözlerine Tematik Yaklaşım
Keywords: North-West (Kipczak) Turkic Dialects and Literatures; Kuzey-Batı (Kıpçak) Türk Lehçeleri ve Edebiyatları